Common genetic variation near MTNR1B contributes to raised plasma glucose and increased risk of type-2 diabetes among Indian Asians. (22nd September 2015) - Chambers, JC; Zhang, W; Sehmi, J; Jain, P; Scott, J; Elliott, P; Kooner, JS
Abstract : Background: Fasting plasma glucose levels are raised, and the risk of type 2 diabetes (T2D) is 2–3-fold higher, among Indian Asians compared with European and north American whites. Although genetic susceptibility is widely reported, few studies have investigated the genetic factors underlying these disturbances of glucose metabolism among Indian Asians. Methods: We carried out a genome-wide association of 582 K autosomal single nucleotide polymorphisms (SNP) for fasting plasma glucose in 5089 non-diabetic Indian Asians (fasting glucose levels <7.0 mmol/l; free from pharmacological or dietary treatment for diabetes), using the Illumina Hap610 BeadChip. Replication and further testing of top-ranking associations was carried out in a separate sample of 1701 non-diabetic Indian Asians and 684 Indian Asians with T2D. Results: We identified and replicated association of SNP rs3847554 near MTNR1B with glucose levels (combined p = 1.3 × 10 −10 ). The risk allele of SNP rs3847554 was also associated with raised haemoglobin A1c, reduced HOMA-B and an increased risk of T2D compared with wild type (odds ratio 1.17, p = 0.01). The risk allele frequency of rs3847554 is higher among Indian Asians (49.8%) than the HapMap CEU population (40.0%, p<0.001). Conclusions: A common genetic variation near MT1NRB influences blood glucose, and is associated with an increased risk of T2D in Indian Asians. Our findings suggest that abnormalities of melatonin signalling may be an important mechanism contributing to the current world-wide epidemic of T2D and related metabolic and cardiovascular disorders among Indian Asians.